Imago proelii. La cartografia storica della Prima Guerra Mondiale dal Museo Storico della Terza Armata: spigolature per una analisi tipologica e semiologica - Elena Dai Prà; Nicola Gabellieri (Bollettino della Società Geografica Italiana, 2021)
International historiography has extensively assessed the innovations in war practice experienced during the First World War. However, the consequences of trench warfare in military cartographic production have not been fully investigated yet. Following this line, the essay presents the cartographic corpus of the historical archive of the Terza Armata (Third Army); the Terza Armata had a fundamental role in the conflict, settling on the Piave river after Caporetto and leading the final advance towards Istria. The analysis of the collection, which is still unpublished, can open a new front of research aimed at developing categories of semiological analysis and typological classification of military maps as sources produced in fieri, i.e. manuscript IGM maps that were constantly updated during war operations. First, the cartographic corpus is presented; second, a first typological classification and a semiological decoding of maps are proposed, based on the interpretation of the symbols used, of the legend and of the methods of representation. In particular, the contribution focuses on tactical maps, i.e. cartographies that were continuously updated in proelio to document the evolution of war events on the front line.